Influence of Learning Attitudes, Ethics, and Peer Interaction on Students’ Entrepreneurial Behavior - Ayu Trisnawati; Elpisah Elpisah; Saripuddin Saripuddin; Erni Rismawanti; Suarlin Suarlin (Educational Dynamics: International Journal of Education and Social Sciences, 2025)
This study aims to examine the influence of learning attitudes, student ethics, and peer interaction on entrepreneurial attitudes among Grade VII students at SMP Negeri 6 Bulukumba. A quantitative research method was applied with a saturated sampling technique involving 49 students. Data were collected through questionnaires and analyzed using multiple regression, t-test, and F-test in SPSS 26. The results show that each independent variable—learning attitude, ethics, and peer interaction—has a significant positive impact on students’ entrepreneurial attitudes. Collectively, these variables also significantly influence entrepreneurial behavior. The study emphasizes the importance of academic, ethical, and social factors in promoting entrepreneurial mindset in secondary education settings.